(untitled) (KULT_online, 2019)
The edited volume Christian Krachts Weltliteratur. Eine Topographie by Stefan Bronner and Björn Weyand (ed.) uses an expansive concept of world literature to describe an author’s work which includes more and more diverse topographies in its texts, and which refers to the world in an ambivalent manner, as taking place between fact and fiction, life and literature, self-reference and context. Furthermore, Kracht’s travel writing and co-authored texts are brought into focus and can now be observed as being part of and interacting with his novels.